Optimal power flow method with consideration of uncertainty sources of renewable energy and demand response - Zhang, Wenjia; Peng, Zhuyi; Wang, Quanquan; Qi, Wanchun; Ge, Yi (Frontiers in Energy Research, 2024)
Existing research on optimal power flow (OPF) calculation methods has focused primarily on the design and improvement of probabilistic calculation methods, neglecting the impact of demand response on online security calculation of power systems with renewable energy sources. Therefore, this paper proposes an OPF calculation method that considers the uncertainties of wind power, photovoltaic (PV) power generation and demand-side response. Firstly, the research focuses on the renewable energy grid, considering the uncertainties of wind power and PV power generation, and establishes uncertainty models for wind power and PV output. Secondly, based on cloud model theory, an uncertainty model for demand response is established. Then, according to the previously established models, an OPF model is constructed and a linearized method for OPF calculation considering multiple uncertainties is also proposed. Finally, taking the IEEE 30-bus system as an example, the effectiveness and superiority of the proposed OPF calculation method are verified.